PERBANDINGAN TINDAK PIDANA PENCURIAN DATA PRIBADI ANTARA NEGARA REPUBLIK INDONESIA DENGAN NEGARA SINGAPURA: Comparison Of Personal Data Theft Criminal Actions Between The Republic Of Indonesia And The State Of Singapore - Emmanuela, Michele; Widjajanti, Ermania (Faculty of Law, Universitas Trisakti, 2024)
Personal data is certain personal data that is stored, maintained, maintained true and protected confidentially. Currently, there is a rampant theft of personal data to get financial benefits. Indonesia regulates in Law Number 27 of 2022 concerning Personal Data Protection which has just been passed. Singapore has had regulations since 2012, namely the PersonaI Data Protection (Amendment) Act No. 40 of 2020. Research is carried out normatively, the nature of analytical descriptive research and drawing deductive logic conclusions. In Indonesia, the crime is regulated in Article 67 of Law Number 27 of 2022 concerning Personal Data Protection and Singapore is regulated in PersonaI Data Protection (Amendment) 2020 section 51. There are 4 similarities and 8 different elements of the criminal act of personal data theft. The focus of discussion in this paper is how to regulate the criminal act of personal data theft, how the similarities and differences in the elements of personal data theft in Indonesia and Singapore.